THE BASIS FOR THE CREATION OF THE DEPICTION DESCRIBED IN THE CHITRASUTRA - Hari Om (ShodhKosh: Journal of Visual and Performing Arts, 2022)
Indian painting is mentioned in various texts. In the Chitrasutra of Vishnudharmottara Purana, as much detail and clear description of painting has been given, it is not found in any other text. The author has considered the work of a painter as a difficult practice. He has described the status of a painter as a yogi. The difference between the two is only that the yogi creates a world to which the common man cannot reach, he does not even imagine enjoying the pleasures of life, the painter enjoys bliss and fame in this material life as well as ecstasy and He also receives the Supreme. Painting is a long practice. The paths of his accomplishment are very difficult, but his results are equally excellent. From the Indian point of view, the best painting has been described as the means of worldly travel and the reason for the transcendental selflessness.